Recent advances in marine ornamental breeding and seed production at Vizhinjam Regional Centre of CMFRI India - Anil, M. K.; Rohini Krishna, M. V.; Gomathi, P.; Surya, S.; Gop, Ambarish P.; Santhosh, B.; Siju, R.; Anand, V.; Krishnapriya, P. M.; Shalini, O.; Raju, B.; Madhu, K.; et al. (Frontiers in Marine Science, 2022)
The marine ornamental fish trading industry is an ever-expanding one which is indicated by its bolstering statistics, which amounts to about US 300 million. Though the trade is booming, the natural habitats that foster these fishes, such as coral reefs, are steadily declining. One of the reasons for this is the overdependency of the industry on wild-caught fishes. To surpass this Central Marine Fisheries Research Institute (CMFRI) centre developed hatchery technology for breeding marine ornamental fishes such as seahorses, clown fishes, damsels and serranids. It began with the breeding of Hippocampus kuda. This progressed to breeding clownfishes such as Amphiprion chrysogaster, Premnas biaculeatus, Amphiprion ocellaris, and Amphiprion nigripes Amphiprion peridarion and Amphiprion ephippium. Damsel fishes that were bred successfully include Chrysiptera cyanea, Neopomacentrus cyanomos, and Neopomacentrus nemurus. Recirculating aquaculture system (RAS) designed in Vizhinjam regional centre, CMFRI is being used for broodstock development of serranids, tangs, squirrel fishes and soldier fishes. A standard method was developed for captive breeding and hatchery rearing of anthias Pseudanthias marcia and P. sqamipinnis in an advanced indigenous RAS system. The present article provides a bird’s eye view of the research work done at Vizhinjam Regional centre of CMFRI concerning marine ornamental fish breeding